Foreign direct investment inflows and labor productivity in Pakistan: A sector-wise panel cointegration analysis - Ayesha Serfraz (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2017)
Developing economies tremendously benefit from FDI inflows since it leads to their economic growth. This study empirically analyzes the effects of sector-wise FDI inflows on respective sector-wise labor productivity for a panel of seven major sectors of Pakistan's economy covering time period of 1997-2016. In empirical analysis sector-wise FDI inflows has been used as an independent variable while sector-wise labor productivity is a dependent variable. Initial tests conclude that LSDV fixed effects model is the most appropriate test for the data being used for empirical analysis. Further tests confirm the existence of a long run Cointegration between these two variables. Wald test shows that a uni-directional short-run causality exists, running from sector-wise labor productivity to sector-wise FDI inflows. Pair-wise Granger-Causality test further shows that the effects of FDI inflows are not limited to one sector, rather there is an evidence of spillover effect from one sector to an-other. All empirical tests conclude that sector-wise FDI inflows positively affect sector-wise labor productivity in case of Pakistan.
Keywords: 330; Sector-wise FDI Inflows; Sectors-wise labor Productivity; Panel Cointegration; Pakistan